What is mathematics? - Ortigas, T. Z. (Education quarterly.)
This paper exhibit the nature of mathematics by describing the structure of some mathematical systems and tracing their origins. The idea conveyed is that mathematics arises out of the social need of man. Born as an empirical science, it grows to a national level where logical structure is built on some fundamental principles abstracted from experiences and observations. By applying the highly abstract ideas to practical situations, mathematics becomes the vehicle that carries science onwards.